Hitchcock as philosopher - Yanal, Robert J. (McFarland & Co., 2005)
"The work discusses 12 Hitchcock films and reads them as raising and putting forth a position on three problem areas of epistemology: deception, knowledge of mind, and problematic knowledge of the external world. Introductions to these philosophical concepts are given, as well as summaries to the films analyzed"--Provided by publisher.